Sacred Journeys: Religious Tourism and Pilgrimage - Chadwick Co Sy Su (Religions, 2018)
Pilgrimage, being an ancient practice and a global phenomenon, continues to gain a growinginterest among scholars as its scope traverses many other disciplines and perspectives.[...]